Pengaruh TAM Terhadap Kepatuhan Wajib Pajak dengan Penggunaan E-Filing Sebagai Variabel Intervening Pada KPP Pratama Sukoharjo - Karmila, Karmila; , Dra. Mujiyati, M.Si (2016)
TAM is one of the teories on the use of information technology systems that are considered very influential and is commonly used todescribe the individual acceptance of the use of information technology system. The purpose of this study was to determine the effect directly and indirectly between TAM on tax compliance through this of e-filing. The population used in this study were 100 taxpayers. Sampling with purposive sampling method. The number of samples used were 67 taxpayers. In the presence of data outliers, the sample as mech as 28 to 39 taxpayers. Analysis used in this research is the analysis path. Based on the results of data analysis showed that the variables TAM and the use of e-filing significantly influence taxpayers compliance. This can be see from thitung > ttabel and probabilities < 0.05. Keywords : TAM, The use of e-filing, Tax Compliance, Analysis Path